Jadīd Panjābī adab : ek savāliyah nishān - Aḥmad Salīm, 1945- (Karācī : Riktāb, 1986)
On contemporary Panjabi literature, 1947-1985; critical study
In Urdu.
Mode of access: Internet.
Keywords: Panjabi literature -- History and criticism